Simulation and Experimental Verification of Microscopic Surface Morphology of Spiral Bevel Gears by Shot Peening - Liao Xianggui; Wu Hao; Tang Jinyuan; Zhao Jiuyue (Jixie chuandong)
The shot peening strengthening process can introduce residual compressive stress field on the surface and subsurface of spiral bevel gears to improve their fatigue life. However, inappropriate process parameters can cause a significant increase in gear surface roughness, which has an adverse effect on the contact performance of the tooth surface. In order to accurately calculate the microscopic morphology and surface roughness of the gear surface after shot peening, this study proposes a spiral bevel gear tooth surface shot peening simulation model based on a coupled discrete element method and the finite element method. The prediction error of the model is within 20%, which illustrates the accuracy of the simulation prediction model. Based on this model, the correlation law between different shot peening process parameters and the microscopic morphology of the tooth surface after shot peening is investigated with a spiral bevel gear of a certain model as the research object. The results of the study show that: the three-dimensional roughness Sa of the tooth surface increases significantly and then decreases slowly as the shot peening time increases. When the shot peening time is 50 s, the full coverage can be achieved by the process parameters in this study. Both shot velocity and shot diameter have a greater effect on the roughness of the tooth surface, but the effect of shot diameter is more significant. The research work in this study provides a new method for accurate numerical simulation and prediction of the microscopic morphology of the spiral bevel gear surface after shot peening, and provides technical support for the reasonable formulation of shot peening process parameters.